Ornebius exserolimbus Wang & Ma, sp. nov., a new species of Ornebius (Orthoptera: Mogoplistidae; Mogoplistinae) from China - Wang, Ning; Che, Zhi-Yong; Ma, Li-Bin (Zootaxa, 2023)
The Mogoplistidae genus Ornebius contains eight species groups and 124 species worldwide, with 14 species recorded from China. Here, we find a new species belonging to the species group alii Bhowmik, 1970 from Yunnan Province, China. The new species, Ornebius exserolimbus sp. nov., is distinct by bearing a protrusion on the anterior margin of the pronotum. This feature was first discovered in scale crickets and it might be related to some special locomotion function of crickets. Besides describing and illustrating the new species, we provide keys for Chinese Ornebius species in this article.